Pelatihan Kewirausahaan : Praktik Mandiri Keperawatan dan Perawatan Luka Modern - Oktarina, Yosi; Subandi, Andi; Sulistiawan, Andika; Mekeama, Luri; Nurhusna, Nurhusna (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This community service aims to increase the knowledge and skills of alumni regarding independent nursing practice and modern wound care. The method of implementing this service used training and demonstration. The partners in this activity were 20 alumni from the Nursing Study Program at the University of Jambi. The instrument used in this activity was a questionnaire on knowledge of independent nursing practice and modern wound care. The data analysis used uses a frequency distribution. The results of this service activity show an increase in knowledge and skills in the excellent category regarding independent nursing practice and modern wound care, which reached 90%. With this activity, it is hoped that more alumni will be able to carry out independent nursing practice. Apart from that, there is a need to strengthen the knowledge and skills of alumni on an ongoing basis.